(untitled) (Social and Environmental Law Journal, 2024)
Young people have been producing and occupying new spaces in political participation. After years of disenchantment with their role in the public arena, they have found ways of participating that do not conform to the mechanisms of classic bureaucratic-rational organizations, such as political parties, nor to various civil society organizations. The emergence of other technologies and social networks has made possible new ways of convening, enunciating, and participating in transversal struggles. These modes of participation have shown that young people are not apathetic regarding political participation, but rather that the ways and issues that concern and interest them are configured differently. The research project from which these reflections arise traces these new ways of doing politics and proposes some possible interpretations in light of recent electoral events that have highlighted how the far-right has used technologies and social networks to position themselves in relation to youth and to craft discourses that are low in content but highly impactful, managing to undermine the foundations of democracy.